Reviewer Acknowledgements and Highlights: Health at Every Stage - GHMJ (Global Health Management Journal), Volume 9, Number 1, 2026 - GHMJ (Global Health Management Journal) (GHMJ (Global Health Management Journal), 2026)
The Editorial Board would like to extend its sincere appreciation to the reviewers who contributed their time and scholarly expertise to the issue of the Global Health Management Journal (Vol. 9, No. 1, 2026). This issue begins with a timely reminder that tackling non-communicable diseases demands shared responsibility and sustained care at every stage of life (Ajeigbe et al., 2026). Innovation runs alongside this theme, from fresh ways to raise awareness of sexual and gender-related violence to powerful images of health initiatives reaching remote communities in Nepal (Besigye et al., 2026; Adhikari et al., 2026). This issue also deeply explores the structural and behavioral determinants of health; from a correlational study on fast food consumption that shaping future health risks (Sulistyowati et al., 2026), to a compelling examination of child marriage reframes with profound global health implications (Macnab, 2026). Moreover, the research articles extend these discussions into behavioral, social, and biomedical domains. Alongside a thoughtful perspective that reexamines youth resilience in Africa through intergenerational care and indigenous support systems (Gasa & Kpum, 2026), the issue raises a best practice study on fresh fish stall businesses supporting nutritional health in Indonesia (Haqiqiansyah et al., 2026). Finally, a laboratory-based research on the antibacterial activity of Muntingia calabura leaf extract reflects the continued importance of scientific inquiry in addressing infectious threats (Fadilah et al., 2026). Link to download: https://publications.inschool.id/index.php/ghmj/issue/view/GHMJ.09.01 Editor-in-chief Prof. Andrew John Macnab Managing Editors Doni Marisi Sinaga, M.Sc. Kukuh Madyaningrana, M.Biotech. Ph.D. Journal Managers Suyitno, M.PHM Maretalinia, M.A  External Reviewers Prof. Duncan Greenlaw, Ph.D. (Kwantlen Polytechnic University, Canada) Ahmad Said, M.Sc. (Sekolah Tinggi Teknologi Cipasung, Indonesia) Esti Krismiyatun, S.Kep.,Ns.,M.Kep.,FISQua (RSUD dr. Doris Sylvanus Palangka Raya, Indonesia) Ficky Adi Kurniawan, S.Pd., M.M.B (Pujiono Centre Yogyakarta, Indonesia) Ns. Ayut Merdikawati, S.Kep., M.Kep. (Universitas Brawijaya, Indonesia) Dr. Erwan Sulistianto, S.Pi, M.Si. (Universitas Mulawarman, Indonesia) Dr. Agi Christiana Ikpoyi (Joseph Sarwuan Tarka University, Nigeria) Supim Wongtongtair, Ph.D. (Srinakharinwirot University, Thailand) As a token of appreciation for the ongoing service to the journal, Perspective and Guest Editorial submission following the ongoing Special Edition will not be subject to any publication fee for one submission per year. We delightedly invite experts to collaborate with us to benefit on our Editorial Board.  Acceptance Rate   : 49 % Days to First Editorial Decision  : 5 days Days to accept  : 56 days Published: 03 March 2026.